Expressive Morphological Skills of Dual Language Learning and Monolingual German Children: Exploring Links to Duration of Preschool Attendance, Classroom Quality, and Classroom Composition - Bihler, Lilly-Marlen; Agache, Alexandru; Schneller, Katja; Willard, Jessica A.; Leyendecker, Birgit (Frontiers in Psychology, 2018)
A growing body of research has been documenting environmental factors that support preschoolers’ vocabulary skills. However, less is known about how environmental factors are related to morphological skills of Dual Language Learners (DLLs) and Single Language Learners (SLLs). We examined connections with preschool experiences by investigating the effects of duration of preschool attendance, classroom quality, and classroom composition variables (percentage of DLLs and percentage of children from families with a low socio-economic status) on preschoolers’ expressive morphological skills. Several multilevel regression models were estimated using cross-sectional data from 835 children (n = 255 DLLs) aged 30 to 47 months. These children were nested in 169 preschool classrooms in Germany. As a control task, we also investigated children’s phonological processing abilities, for which we found, as expected, no differences between DLLs and SLLs. Our main finding was that DLL children scored lower in expressive morphological skills than their German monolingual peers, but this difference was considerably smaller in classrooms that scored high in instructive teacher-child interactions (measured by the Classroom Assessment Scoring System for preschool to kindergarten children; CLASS Pre-K). Taken together, these results support the notion that supportive teacher-child instructive interactions have a positive impact on the development of DLLs’ morphological skills.